Parental involvement in mathematical literacy development: a crosscultural systematic literature review of home-based practices and their impact - Masnaeni Masnaeni; Nursalam Nursalam; Andi Kusumayanti; Andi Ika Prasasti Abrar (Universitas Sarjanawiyata Tamansiswa, 2025)
Parental involvement plays a crucial role in supporting children’s mathematical literacy, a key competence for meaningful participation in twenty-first-century societies. This study seeks to synthesize cross-cultural evidence on the forms, mediating factors, and effects of parental involvement in mathematics learning through a Systematic Literature Review with a qualitative meta-synthesis. Following PRISMA guidelines, 38 peer-reviewed studies published between 2018 and 2025 were identified and analyzed using thematic synthesis. The findings identify six interrelated thematic clusters of parental involvement: home-based academic support; affective and motivational support; home numeracy practices and family math talk; digital and media-based involvement; socio-cultural and economic mediation; and structured school–family partnerships. Across diverse cultural contexts, parental involvement is consistently associated with improvements in children’s conceptual understanding, mathematical reasoning, and positive dispositions toward mathematics. However, the form and effectiveness of such involvement are shaped by cultural values, parental readiness, and socioeconomic conditions. Theoretically, this study advances a culturally grounded conceptual model that clarifies how contextual and mediating factors shape parental involvement pathways to mathematical literacy outcomes. Practically, the findings provide guidance for culturally responsive, family-centered educational policies and interventions aimed at strengthening home school collaboration and reducing inequities in mathematical literacy development.